InvestigatingthePredictiveRoleofFeedingBehavioronDentalCaries - AlirezaRahbar; BatoolAmiri; ZeinabKhojaste; MohammadRezaHosseini; NajmehSavadi (Isfahan University of Medical Sciences, 2024)
Ahealthydietandpropereatinghabitsinchildhoodpromoteoptimaloralhealth.ThisstudyaimedtoevaluatedentalcariesanditsassociationwithfeedingpatternsinchildrenreferredtoBushehrdentalcentersin2022.Materials&Methods:Thiscross-sectionalstudywasconductedon178childrenwhoreferredtoBushehrdentalcentersin1401.TheDMFTindexandthePersianversionoftheFoodFrequencyQuestionnairewereusedtocheckthetoothdecayandthefoodpatternofchildren,respectively.Ahierarchicallinearregressionmodelwasusedtoinvestigatetherelationshipbetweentoothdecayandfoodpatterns;inthisway,thevariablesaffectingcarieswereplacedinfourblocksofdemographicfactors,behavioralfactors,socio-economicfactors,andtheamountoffoodintake,sothatbyadjustingtheeffectofthefirstthreeblocks,theeffectoftheblockoffoodintakeinpredictingtheindicesofdmft,DMFTandthesumofthem(DMFT+dmft)couldbechecked.Results:Thehierarchicallinearregressionresultsshowedthatinthefinalmodel,thevalueoftheadjustedR2fortheDMFT,dmftindicesand,thesumofthem(DMFT+dmft)was0.63,0.98and,0.59,respectively.(pvalue<0.001).Furthermore,thepredictiveroleofthedietarypatternalone(R2change)onDMFT,dmft,andDMFT+dmftindiceswas0.30,0.52and,0.45respectively,whichindicatesahigherpredictiverolethanbehavioral,demographicand,socioeconomicfactors.Conclusion:Thestudyfoundaconfirmedrelationshipbetweentoothdecayandfeedingpatterns.Itwasalsoobservedthatfeedingpatternshavethegreatestimpactonthedecayofdeciduous,permanentteeth,andbothoftheminchildrenofthisagegroup.Demographiccharacteristics,socioeconomicstatusofthefamily,andbehavioralcharacteristicswererespectivelyinthenextlevelsandplayedalesserroleinthedeteriorationoftheseindicators